Penerapan Metakognetif Sebagai Strategi Pembelajaran Mandiri Siswa Dalam Pembelajaran Bahasa Arab - Aliyah Aliyah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2018)
Metacognitive is a word that relates to what is known about him as an individual who learns and how he controls and adjusts his behavior. Someone needs to be aware of the shortcomings and advantages they have. Metacognitive is a form of ability to look at yourself so that what he does can be optimally controlled. To find out the metacognitive students, the teacher must train them to 1) design what they want to learn, 2) monitor the progress of student learning, 3) assess what has been learned. By knowing the cognition of each student, self-learning can be carried out independently, with independent learning the complex components of Arabic will be studied maximally.